Nutrition of Tithonia diversifolia and attributes of the soil fertilized with biofertilizer in irrigated system - Matheus M. Reis; Leonardo D. T. Santos; Rodinei F. Pegoraro; Fernando Colen; Leonardo M. Rocha; Guilherme A. de P. Ferreira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The fertilization with biofertilizer associated with the use of irrigation favors nutrient uptake by plants and soil chemical properties; however, these effects are little studied in Tithonia diversifolia in semiarid regions. This study evaluated the effect of doses of bovine biofertilizer and irrigation on accumulation of nutrients in the leaves of Tithonia diversifolia plants and on soil chemical attributes. The study was carried out from December 3, 2014 to November 28, 2015, and arranged in a 2 x 5 factorial scheme, consisting of five doses of bovine biofertilizer (0, 40, 80, 120 and 160 m3 ha-1), combined with and without irrigation. The experiment was set in a randomized block design, using three replicates. Irrigation promoted increased accumulation of N, P, K, Ca, Mg, S, Zn, Fe, Mn, Cu and B in leaves of Tithonia diversifolia in the first cutting. However, the high bicarbonate concentration in the irrigation water and the occurrence of rainfall during the second crop increased the accumulation of Cu in the leaves of Tithonia diversifolia under rainfed condition, compared with irrigated plants. The increase in biofertilizer doses contributed to the increment of base saturation and the contents of organic matter, P and K in soil.